Development of effective antimicrobial cocktails to prevent bacterial contamination of allograft tissues under low temperature conditions. (9th July 2018) - Nakaminami, Hidemasa; Tajima, Misa; Koishikawa, Koji; Shiratori, Yuma; Shioura, Mana; Sasatsu, Masanori; Noguchi, Norihisa
Abstract: OBJECTIVES: Prevention of bacterial transmission in recipient patients via allograft decontamination with an antimicrobial cocktail consisting of cefmetazole (cefoxitin), vancomycin, lincomycin and polymyxin B is an important procedure commonly practised in tissue banks. However, some allografts are lost due to the failure of decontamination under low temperature conditions. Here, we aimed to develop new antimicrobial cocktails that exert a high bactericidal activity at 4°C. METHODS: Bacterial species used in this study were selected as major causative pathogens of allograft tissue contamination. The efficacy of the combination of 2 antimicrobial agents was determined by the checkerboard titration method. The bactericidal effects of the new antimicrobial cocktails were evaluated under the same conditions as those used for the storage and preservation of allograft tissues. RESULTS: Among the selected antimicrobial agents, daptomycin exhibited the highest bactericidal activity against methicillin-resistant Staphylococcus aureus under low temperature conditions. The combination of daptomycin + gentamicin and daptomycin + levofloxacin showed a synergistic or additive effect against various bacterial species. The antimicrobial cocktail containing 200 μg/ml of daptomycin, gentamicin and levofloxacin could eradicate ≤10 4 colony-forming units/ml of methicillin-resistant S. aureus and Enterococcus faecalis, which exhibit a low susceptibility to antimicrobial agents at 4°C for 24 h. CONCLUSIONS: We have developed a new formula for an antimicrobial cocktail to effectively and sufficiently prevent bacterial contamination of allograft tissues under low temperature conditions in vitro .